Influence of exercise-induced plasma volume changes on the interpretation of biochemical data following high-intensity exercise - Kargotich, S.; Goodman, C.; Keast, D.; Fry, R. W.; Garcia-Webb, P.; Crawford, P. M.; Morton, A. R. (Clinical Journal of Sport Medicine, 1997)
OBJECTIVE: To assess the effects that exercise-induced plasma volume changes (PVCs) have on the interpretation of biochemical and hormonal parameters in the blood of athletes after high-intensity exercise. It was hypothesized that two unrelated high-intensity exercise protocols, performed by two separate subject groups each using different exercise modes, would result in similar percentage changes in plasma volume (% delta PV). It was further hypothesized that the % delta PV, measured in both protocols, would comparably influence the interpretation of biochemical variables measured following exercise. DESIGN: An experimental before-after trial on volunteers was performed. Two different exercise modes employing two different high-intensity acute exercise protocols were investigated. Eight male swimmers performed an interval training session (ITS) consisting of 15 x 100-m freestyle efforts at 95% of their maximal exercise intensity, and eight male runners performed a multistage discontinuous treadmill test (MSD) to volitional exhaustion. SETTING: The Human Performance Laboratory at the Department of Human Movement at the University of Western Australia. MAIN OUTCOME MEASURES: Blood samples obtained before, immediately after, and 30, 60, and 120 min during recovery were analyzed for plasma volume changes, urea, uric acid, creatinine, albumin, calcium, iron, transferrin, testosterone, cortisol, and sex hormone-binding globulin (SHBG). MAIN RESULTS: The ITS and MSD protocols produced similar and significant alterations (p < 0.01) in plasma volume. Both protocols also elicited significant fluctuations (p < 0.01) in the concentration of most of the parameters measured (excluding iron). When albumin, transferrin, testosterone, and SHBG values were adjusted for the significant % delta PV, their concentrations did not change over the experimental period, suggesting that the changes in measured concentration of these parameters may be, in part, due to changes in plasma volume. However, urea, uric acid, creatinine, calcium, and cortisol, when corrected for % delta PVC, still demonstrated significant changes (p < 0.01). CONCLUSIONS: It is recommended, when sampling biochemical and hormonal parameters in blood following an acute bout of exercise, that corrections for PVCs should be conducted. Apparent changes in blood solutes may reflect PVCs. PVCs should be taken into consideration when interpreting results regardless of exercise protocol and exercise mode performed.